BJOG Editor's Choice. (22nd September 2016) - Chien, Patrick
Abstract : Editor‐in‐Chief, Professor Patrick Chien, discusses his top articles from this issue in an audio podcast available at:https://soundcloud.com/bjog/october-editors-choice-2016 .